Study on the factors influencing lens opacity among medical radiation workers exposed to long-term low-dose ionizing radiation - Ye, Anfang; Li, Jianing; Hao, Xiaoji; Lai, Zhongjun; Guo, Jiadi; Cao, Yiyao; Yu, Shunfei; Xuan, Zhiqiang (Frontiers in Medicine, 2025)
BackgroundLens damage induced by occupational exposure to ionizing radiation has been extensively studied by radiation workers. This study aimed to investigate the factors influencing lens opacity in radiologists exposed to low-dose ionizing radiation.MethodsMedical examination data of 1,456 radiological workers who underwent occupational health checkups between January 2023 and December 2024 were collected, along with their total personal radiation dose over a 10-year period from 2015 to 2024. The relationship between lens opacity and influencing factors such as sex, age, radiation dose, occupational type, and duration of radiation work was analyzed using multivariate logistic regression.ResultsAmong the 1,456 radiological workers, 105 cases of lens opacity were detected, with a prevalence rate of 7.21%. The majority of lens opacities were located in the posterior subcapsular region, accounting for 52 cases (49.52%, 52/105). The prevalence of lens opacity revealed a linear increasing trend with age and years of service. In addition, the proportion of lens opacity gradually increased with increasing total and annual radiation doses. Age, occupational type, and total radiation dose were associated with posterior subcapsular opacity. Age and total radiation dose were regarded as independent risk factors [age Odds Ratio (OR), 1.068; 95% confidence interval (CI), 1.035–1.103; total dose OR, 1.111; 95% CI, 1.033–1.194]. The three occupational types with the highest prevalence were nuclear medicine (6/51), radiation therapy (14/240), and interventional radiology (18/340).ConclusionThe prevalence of lens opacity among radiological workers was associated with age, radiation dose, occupational type, and duration of radiation work. Nuclear medicine poses the highest risk for posterior subcapsular opacity.